İndividuals’ Opinions Regarding Reasons For Changing And Editing Their Names-Surnames - Çoban, Vedat; Sunkar, Zeynep; Altın, Ece (Fırat University, 2021)
The present study attempts to determine the reasons that lead people to change and correct their names. Also, it was aimed to evaluate the findings regarding the criteria by which individuals chose their new names during such changes. Names have had quite an important place in people’s lives from past to present. Names have variable qualities that reflect the socio-cultural structure people live in. The Turkish phrase “ismiyle müsemma olmak – being true to one’s name” shows the importance of names in our culture. The emergence of negative factors affecting the perception of an individual who believes that his/her name and surname add value to him/her brings about seeking for a change of name-surname. In this study conducted with the qualitative research method, the data were obtained through face-to-face interviews with fifty people who changed their names or surnames, as a sample group. According to the findings obtained, in addition to the changes made in the Civil Registry Services Act, the increase in communication speed, developments in the media, and the effect of popular culture become prominent in the change of names or surnames. It is seen that socio-cultural differences, new tendencies, attitudes, and group identities are effective in cases of name-surname change depending on the request of the persons.

Bu çalışmada insanları ad-soyadlarında değişime ve düzeltmeye götüren sebepler tespit edilmeye çalışılmıştır. Ayrıca bu değişimde bireylerin yeni adlarını seçerken hangi kriterleri esas aldıklarına yönelik bulguların belirlenmesi hedeflenmiştir. Kişi ad-soyadları geçmişten günümüze insanların yaşamında çok önemli bir yere sahip olmuştur. Ad-soyadları, içinde bulundukları sosyo-kültürel yapıyı yansıtan değişken niteliklere sahiptir. Türkçedeki “ismiyle müsemma olmak” ifadesi, adların kültürümüzdeki önemini göstermektedir. Taşıdığı ad ve soyadının kendisine bir değer kazandırdığına inanan bireyin algısını etkileyecek olumsuz faktörlerin oluşması, ad-soyad değişimi arayışlarını beraberinde getirmiştir. Nitel araştırma yöntemiyle hazırlanan bu makale çalışmasında örneklem grubu olarak ad veya soyadında değişime gitmiş elli kişi ile yüz yüze görüşerek veriler toplanmıştır. Elde edilen bulgulara göre ad veya soyadların değişiminde Nüfus Hizmetleri Kanunu’nda yapılan değişiklikler ile iletişim hızındaki artış, medyadaki gelişmeler ve popüler kültürün etkisi öne çıkmaktadır. Kişilerin isteğine bağlı olarak gerçekleşen ad-soyad değişikliğinde sosyo-kültürel farklılaşmalar, yeni eğilimler, tutumlar ve grup kimliklerinin etkili olduğu görülmüştür.
BİREYLERİN AD-SOYAD DEĞİŞTİRME VE DÜZELTME NEDENLERİNE İLİŞKİN GÖRÜŞLERİ